Bernstein-Jorgens Theorem for a Fourth Order Partial Dierential Equation (Journal of Partial Differential Equations, 2002)
We introduce a metric, conformal to the affine metric, on a convex graph, and consider the Euler equation of the volume functional. We establish a priori estimates for solutions and prove a Bernstein-Jörgens type result in the two dimensional case.
Keywords: Bernstein theorem; fourth order partial differential equations